2022
DOI: 10.1021/acs.energyfuels.2c02093
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Nanoscale Microstructure Diversity of Different Rank Coals

Abstract: The gas flow pattern of the coal seam is closely related to the pore structure of the coal. In order to better understand the pore distribution in different coal samples, the pore distribution and fractal dimension characteristics of five coal samples with different degrees of metamorphism were investigated and analyzed by using the low-temperature nitrogen adsorption method and CO2 adsorption methods based on the fractal theory. The results showed that the higher the degree of metamorphism, the better the por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…An experiment using a flame-retardant electric heating belt ( 9) and intelligent digital display temperature controller (10) for constant temperature control was conducted, and the experimental temperature was constant at 28.5 °C. The vacuum pump (12) was connected to degas the experimental system and the coal sample tank, and the three groups of raw coal were degassed for the first time until the vacuum gauge (13) showed a stable number for more than 1 h.…”
Section: Vacuum Degassing Of the Coalmentioning
confidence: 99%
See 1 more Smart Citation
“…An experiment using a flame-retardant electric heating belt ( 9) and intelligent digital display temperature controller (10) for constant temperature control was conducted, and the experimental temperature was constant at 28.5 °C. The vacuum pump (12) was connected to degas the experimental system and the coal sample tank, and the three groups of raw coal were degassed for the first time until the vacuum gauge (13) showed a stable number for more than 1 h.…”
Section: Vacuum Degassing Of the Coalmentioning
confidence: 99%
“…To improve the utilization rate of CBM and reduce the disaster-causing degree of deep coal seam gas, it is necessary to precisely measure the reserve content of CBM. At present, the main methods commonly used to measure CBM content are direct and indirect. In the process of gas content measurement experiments, many experts and scholars have found that the gas adsorption and desorption curves could not completely coincide in the study of indirect gas content measurement, and there was a phenomenon of gas desorption hysteresis, that is, there is “residual gas” in the gas desorption process within the identical desorption time as the gas adsorption time, which is not in line with the traditional conclusion that the gas adsorption and desorption process is completely reversible. At present, scholars have studied the factors affecting the hysteresis phenomenon of gas adsorption and desorption in coal, as well as the mechanism of the hysteresis phenomenon of the gas adsorption–desorption process in coal, and concluded that the expansion and contraction of the coal matrix, the pore structure, and the change of the potential field of adsorption have a certain influence on the hysteresis phenomenon of gas adsorption–desorption. Wang et al demonstrated the presence of nonresorbable residual gas during gas desorption by gas slow desorption experiments and adsorption hysteresis experiments, and the analysis proposed that the residual gas was due to the bondage of closed or semiclosed pores in the coal. Nemcik et al suggested that there are two reasons for the hysteresis phenomenon of gas desorption in coal: one is the adsorption performance or structural changes of coal; the second is the capillary coalescence phenomenon in the micropores of coal.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, due to the sudden, dangerous, and concealed nature of coal and gas outbursts, only limited information related to the process can be obtained in the field [20][21][22][23], but this information is the key factor to study the mechanism of the outburst. While the mechanism of the outburst has been studied from the macroscopic phenomenon by establishing physical or mathematical models to describe and quantify its unique physical structure, the coal at the microscopic scale also has unique physical characteristics and the outburst process is closely related to it [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental methods used for testing the microstructural changes in coal include high-pressure mercury intrusion, low-temperature liquid nitrogen adsorption, low-pressure CO 2 adsorption, and low-field nuclear magnetic resonance (LNMR). Among these, the high-pressure mercury intrusion, low-temperature liquid nitrogen adsorption, and low-pressure CO 2 adsorption methods cause secondary damage to the coal, which affects the accuracy of the experimental results, while the LNMR method is nondestructive, continuous, and quantifiable, and it better reflects the pore size distribution of the coal. In this study, coal was soaked with supercritical CO 2 , and LNMR was used to characterize the microstructural changes of coal. The LNMR experiment determines the T 2 distribution of dry, water-saturated, and centrifugal coal samples.…”
Section: Introductionmentioning
confidence: 99%